THE COMPOSITION OF THE PECTORALIS MUSCLES OF SOME PASSERINE BIRDS - Salt, W. Ray (Canadian Journal of Zoology, 1963)
Although both the pectoralis major and the pectoralis minor muscles of a number of species of passerine birds are red in color, the pectoralis majors are composed of only one type of fiber, a dark fiber, while the pectoralis minors are composed of dark and pale fibers. The two fibers differ in size and in fibrillar and non-fibrillar content. In the pectoralis minor muscles of the snow bunting, Plectrophenax nivalis, the ratio of dark to pale fibers is about two to one but this ratio differs in other species. It is suggested that the two types of fiber serve different functions in the pectoralis muscles and thus affect the mode of flight.